Au‐NP‐Decorated Crystalline FeOCl Nanosheet: Facile Synthesis by Laser Ablation in Liquid and its Exclusive Gas Sensing Response to HCl at Room Temperature. Issue 9 (10th February 2016) - Wang, Yingying; Zhang, Hongwen; Zhu, Yudong; Dai, Zhengfei; Bao, Haoming; Wei, Yi; Cai, Weiping
Abstract : Here an alternative preparation route, pulsed laser ablation in liquid (LAL) of FeCl3 solution, is reported to facilely synthesize crystalline iron oxychloride (FeOCl) nanosheets at ambient conditions. Well‐dispersed spherical gold (Au) nanoparticles (NPs) are simultaneously decorated on surface of the FeOCl nanosheets, which possess (010) preferred orientations with microsized dimensions in planar and tens of nanometers in thickness. The crystalline size and composition of the Au/FeOCl can be effectively modulated by simply changing FeCl3 concentrations. Technical observations illustrate that the nanocomposites possess good thermal stability and surface of which adsorbs abundant H2 O molecularly and oxygen species chemically. The FeOCl nanosheets are formed through chemical side hydrolysis reaction in the localized liquid region with gradient temperature, which is derived from thermal transfer of LAL‐induced plasma plume. The Au/FeOCl nanocomposites, as chemiresistors, show exceptionally high sensing response and perfect selectivity to HCl gas at room temperature. The excellent sensing behavior is ascribed to the Au‐NP‐enhanced surface chemisorption of oxygen species and selective adsorption of HCl for FeOCl nanosheets. The synthesized Au/FeOCl nanocomposites provide a new candidate for exclusive HCl detection. And the proposed LAL‐assisted fabrication routes might open new perspectives for formation of other metal oxychloride compounds. Abstract : Au‐nanoparticle‐decorated FeOCl nanosheets are facilely synthesized by laser ablation in FeCl3 solution at ambient conditions. The Au/FeOCl nanocomposites are crystalline, thermally stable, and adsorb abundant H2 O species molecularly and oxygen species chemically on the surface. The Au/FeOCl based chemiresistor shows high sensing response and perfect selectivity to HCl gas at room temperature, which can be applied as exclusive HCl detection.